Production of 3-hydroxypropionic acid from glucose and xylose by metabolically engineered Saccharomyces cerevisiae - Kildegaard, Kanchana R. (Metab Eng Commun, 2015)
Biomass, the most abundant carbon source on the planet, may in the future become the primary feedstock for production of fuels and chemicals, replacing fossil feedstocks. This will, however, require development of cell factories that can convert both C6 and C5 sugars present in lignocellulosic biomass into the products of interest. We engineered Saccharomyces cerevisiae for production of 3-hydroxypropionic acid (3HP), a potential building block for acrylates, from glucose and xylose. We introduced the 3HP biosynthetic pathways via malonyl-CoA or β-alanine intermediates into a xylose-consuming yeast. Using controlled fed-batch cultivation, we obtained 7.37±0.17 g 3HP L(−1) in 120 hours with an overall yield of 29±1% Cmol 3HP Cmol(−1) xylose. This study is the first demonstration of the potential of using S. cerevisiae for production of 3HP from the biomass sugar xylose.